2015
DOI: 10.1104/pp.15.00410
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Chlorinated Auxin Is Restricted to the Fabaceae But Not to the Fabeae

Abstract: Auxin is a pivotal plant hormone, usually occurring in the form of indole-3-acetic acid (IAA). However, in maturing pea (Pisum sativum) seeds, the level of the chlorinated auxin, 4-chloroindole-3-acetic acid (4-Cl-IAA), greatly exceeds that of IAA. A key issue is how plants produce halogenated compounds such as 4-Cl-IAA. To better understand this topic, we investigated the distribution of the chlorinated auxin. We show for the first time, to our knowledge, that 4-Cl-IAA is found in the seeds of Medicago trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…There are different studies about the occurrence and endogenous concentration of 4-Cl-IAA in other plant species. Pless et al [15] found the auxin in fully developed leaves of broad beans in high concentrations, whereas in recent studies only small concentrations could be detected, e.g., in young and ripe seeds of beans, respectively [16]. Chlorinated IAA has also been described in other leguminous plants, such as Medicago truncatula and Trifolium repens [16].…”
Section: Introductionmentioning
confidence: 98%
“…There are different studies about the occurrence and endogenous concentration of 4-Cl-IAA in other plant species. Pless et al [15] found the auxin in fully developed leaves of broad beans in high concentrations, whereas in recent studies only small concentrations could be detected, e.g., in young and ripe seeds of beans, respectively [16]. Chlorinated IAA has also been described in other leguminous plants, such as Medicago truncatula and Trifolium repens [16].…”
Section: Introductionmentioning
confidence: 98%
“…Parochetus) tribes we analyzed dry seed extracts from the perennial species C. echinospermum (a wild relative of C. aeritinum), Galega officinalis, Parochetus communis and 2 additional species within the Astragalean clade (Astragalus sinicus and A. propinquus) using base hydrolysis (to hydrolyse auxin conjugates) and UPLC-MS/MS as described previously. 6 Chlorinated auxin was not detected in any of these species (Table 1), although all contained IAA, with the level in P. communis being remarkably high (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent discovery of 4-Cl-IAA in the seeds of Medicago truncatula, Melilotus indicus and 3 Trifolium species has pushed the number of recognized 4-Cl-IAA-producing leguminous species to 14 and extended our detection of this hormone beyond species of the tribe Fabeae, to which this hormone was previously thought to be restricted. 6 It is surprising that the ability of these species to produce chlorinated auxin had remained unrecognised, given that clovers (Trifolium species) have a long cultivation history due to their agricultural significance, especially in temperate regions as forage crops 7 ; and that Medicago truncatula is a model species with a sequenced genome. While the phylogenetic relationships of taxa within the Fabaceae have been somewhat enigmatic, the reconstruction of a phylogeny based on the analysis of the plastid MATK gene resolves many well-supported subclades within the legume family.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations